OP0139-HPR Reducing arthritis fatigue - clinical teams (RAFT) using cognitive-behavioural approaches: an rct. (15th June 2017) - Hewlett, S; Ambler, N; Almeida, C; Blair, P; Choy, E; Dures, E; Hollingworth, W; Kadir, B; Kirwan, J; Plummer, Z; Rooke, C; Thorn, J; et al.
Abstract : Background: RA fatigue is common. Group Cognitive Behavioural Therapy by CBT therapists is effective 1 but few rheumatology teams have psychologists, thus we trained rheumatology teams to deliver RAFT, a cognitive behavioural approach (CBA). Objectives: To test if usual care plus a group CBA course for RA fatigue delivered by rheumatology teams reduces fatigue impact more than usual care alone, in a randomised controlled trial. Methods: A pair of rheumatology nurses/OTs in each of 7 UK hospitals were trained in RAFT. RAFT is 6, weekly 2hr group sessions and a consolidation session (wk 14). Links between thoughts, feelings and behaviours (pacing, communication, sleep, stress) are addressed, with daily diaries of energy expenditure and weekly goal-setting. Usual care was a 5min discussion of the Arthritis Research UK fatigue booklet. Entry criteria were RA, Bristol RA Fatigue (BRAF-NRS) severity ≥6/10 and no recent major medication change. Primary outcome was fatigue impact (BRAF-NRS impact, 0–10) at 26 wks; plus wider aspects of fatigue (BRAF-Multi-Dimensional Questionnaire), pain, disability, sleep, quality of life, mood, self-efficacy, patient global opinion, valued life activities & disease activity. Intention-to-treat regression analysis involved adjustment for baseline scores and centre. Results: 308/333 randomized patients completed 26 wks. The 25 who withdrew had similar (10yr) disease duration but were older (69 vs 62.4 yrs). Baseline fatigue impact was similar for RAFT (n=156, BRAF-NRS 7.10, SD 1.7) and controls (n=152, 7.23, SD 1.6), as were all clinical variables. At 26 wks the RAFT arm had significantly less fatigue impact than controls (BRAF-NRS 5.74, SD 2.4 vs 6.36, SD 2.4). Mean BRAF-NRS impact was reduced by -1.36 (p<0.001) in RAFT vs -0.88 in controls (p<0.004). Regression analysis showed the difference between changes in fatigue impact NRS was -0.59 in favour of RAFT (CI -1.11, -0.06). Regression analysis also showed significant differences in secondary outcomes in favour of RAFT: BRAF-MDQ total fatigue -3.42 (CI -6.44, -0.39); Living with Fatigue -1.19 (CI -2.17, -0.21); Emotional Fatigue -0.91 (CI -1.58, -0.23); and RA self-efficacy (RASE, +3.05, CI 0.43, 5.66). There were no differences between arms for changes in fatigue severity or other clinical variables. 99% of RAFT patients would definitely recommend the course to others compared to 50% controls (p<0.001). 90% of RAFT patients rated satisfaction ≥8/10 (including 62% rating 10/10); in comparison 50% controls rated satisfaction ≥8/10 (including 26% rating 10/10, (p<0.0001). Over 26 weeks 20 control patients sought extra appointments for fatigue help compared to 8 RAFT patients (14.2% vs 5.3%, p<0.01). Conclusions: Rheumatology teams delivering a manualized CBA group intervention addressing fatigue impact, not only improve RA fatigue impact, but also emotional & overall fatigue, living with fatigue and self-efficacy, with very high patient satisfaction. Providing rheumatology teams with CBA skills is a potential new therapeutic approach to change practice and improve patient outcome. References: Hewlett et al, ARD 2011;70:1060–7. Disclosure of Interest: None declared